Defense Mechanisms, Gender, and Adaptiveness in Emerging Personality Disorders in Adolescent Outpatients. Issue 12 (December 2020) - Di Giuseppe, Mariagrazia; Perry, John Christopher; Conversano, Ciro; Gelo, Omar Carlo Gioacchino; Gennaro, Alessandro
Abstract : Abstract: The present study focused on demographic and personality differences in the use of 30 defense mechanisms in adolescents with personality psychopathology and explored the hierarchical organization of personality traits based on the adaptiveness of defensive functioning. A total of 102 self-referred adolescent outpatients were interviewed and assessed on defense mechanisms and personality traits using the Defense Mechanisms Rating Scales and the Shedler-Westen Assessment Procedure 200 for Adolescents, respectively. Age and gender differences were found throughout the hierarchy. Pearson's correlations revealed a hierarchical organization of emerging personality disorders (PDs) in adolescence. More adaptive defenses were clearly associated with healthier personality style, whereas more pathological personality styles such as those with borderline traits were characterized by more rigid and maladaptive defenses. Dissociation was also associated with maladaptive personality types. Identifying the defenses associated with emerging personality disorders may inform the unconscious function of defense mechanisms in specific PDs. The systematic assessment of defense mechanisms might also help therapists to monitor changes during treatment.